PENCEGAHAN PENYAKIT DIABETES MELLITUS MELALUIPROGRAM PENYULUHAN DAN PEMERIKSAAN KADAR GULA DARAH DI DUKUH CANDRAN DESA SENTONO KLATEN JAWATENGAH - Jamalul Lail (Asian Journal of Innovation and Entrepreneurship, 2014)
Diabetes Mellitus (DM) is one of disease that frequently occurs in Indonesia.Generally, diabetes mellitus is characterized by increased blood sugar levels. Diabetesmellitus is not only a disease that spread in urban areas but also has now become adisease that is spreading in rural areas. The spread of diabetes up to the village is verythreatening to the public health conditions in the village. This is because knowledge ofthe villagers about the disease diabetes mellitus in terms of the causes or signs for thesufferer was low. As was the case in the dukuh Candran, Sentono village, Klaten ,Central Java.Residents in the dukuhCandrandonot understand diabetes mellitus andhow the examination and treatment. Under these conditions, the program of diabetesmellitus and checkingblood sugar levelswas held in the dukuh  Candran with the aimthat the citizens can gain knowledge of diabetesmellitus on the characteristics of thedisease, how to inspection, to how the disease anticipates.